MICROBIOLOGICAL EVIDENCE OF Helicobacter pylori FROM PATIENTS SUFFERING FROM GASTRODUODENAL DISEASE (Sciences & Technologie. C, Biotechnologies, 2016)
Studies of gastric biopsies taken from ten hospitalised patients suffering from gastroduodenal diseases and were subjected to a oesogastroduodenal fibroscopy, with a fast urease test, histological, cytological examination and a microbiological culture make the evidence of H.pylori. ¶We had isolated H.pylori from seven patients among the ten patients having an infection with H.pylori announced by histology and urease test. H.pylori ¶identification was based on the morphological and biochemical characters. Our ¶research was reinforced by the realization of an antibiogram which can guide us towards an antibiotherapy for the eradication of H.pylori infection.